The Influence of Politics and Law on the Sustainability of Water Resources in the Cigugur Region, Kuningan Regency - Budiyanti, Setia; Hidayat, Dudung; Yusup Permana, Deni; Karmenita, Karmenita; Wiranata, Fahad (Jurnal Legisci, 2025)
Background. Water resources need a legal umbrella so that they can be utilized for the prosperity of many people. The participation of the Government and the community is necessary in maintaining the sustainability of water resources. Aim. This research aims to (1) explore the influence of legal politics on the sustainability of water resources in Cigugur, (2) identify the main challenges faced by indigenous peoples in protecting their water sources, and (3) design effective legal solutions to strengthen the protection of water resources. Methods. The research method used is normative juridical, which includes literature studies, in-depth interviews with local stakeholders, and analysis of existing policies. With this approach, the research seeks to provide a comprehensive overview of the political dynamics of law and the challenges faced by indigenous peoples. The research output is expected to meet the Technology Readiness Level (TKT) 1 in the field of social humanities. Result. The results of this research are expected to be not only academically useful but also have practical implications in helping the Cigugur indigenous people maintain the sustainability of their water resources amid the challenges of modernization and climate change. Conclusion. This study shows that legal politics in water resource management in Cigugur, Kuningan Regency, has not fully supported the preservation of water resources due to the lack of integration between modern policies and the local wisdom of indigenous peoples. Local wisdom, such as leuweung larangan and ci-lemah cai, which have proven effective in maintaining aquatic ecosystems, have not been well accommodated in existing policies. Therefore, more inclusive and sustainable legal policies are needed to integrate the traditional values of indigenous peoples, update outdated regulations, increase community participation, and ensure ecological and social sustainability for the protection of water resources. Implication. Sustainable water resources need good public policy under environmental law.